Prognostic value of hyponatremia in critically ill children admitted to the pediatric intensive care unit - Hanchinmani, Arpana; Kamble, Dnyanesh Duryodhan; Patil, Vishwanath Dundappa (Indian Journal of Child Health, 2018)
Background: Hyponatremia is the most common electrolyte disturbance in critically ill children. Although hyponatremia in hospitalized children is associated with adverse outcomes, the risk can be reduced by early diagnosis and intervention. Objective: The objective of this study is to identify the outcome of hyponatremia in critically ill children seeking emergency care in the pediatric intensive care unit (PICU). Methods: Demographic data, detailed history, systemic examinations, and routine blood and urine investigations were conducted if required for 100 critically ill children aged 1 month